DETERMINASI TEKNIK RENANG GAYA PUNGGUNG SISWA - Indah Purnama Sari; Umar Umar; Maidarman Maidarman; Ronni Yenes (JOLMA, 2021)
The problem in this study is that there are still many technical errors made by students when doing breaststroke swimming. This study aims to dnik etermine the level of breaststroke swimming technique among students of the UNP Faculty of Science and Technology Coaching Department. This typepunggung of research is descriptive research. This research was conducted in December 2020 at the FIK UNP Swimming Pool Gor. The study population was all students majoring in coaching who took the deepening swimming course for the June - December 2020 semesters as many as 33 people. The sampling technique used in this study was purposive sampling technique, so the sample size of this study was 16 students. The instrumentation in this study used the breaststroke swimming technique assessment format. The data analysis technique in this study used descriptive statistical analysis techniques percentages.The result of the research is the level of mastery of breaststroke swimming technique skills (71.4%), belonging to the Good category, meaning that the average student has mastered the breaststroke swimming technique skills according to the proper rules.